Keyword Based Learning in Writing Poetry Skills with Influence of Students’ Motivation and Teaching Skills of Teachers (Universitas Negeri Semarang, 2018)
The purpose of this study is to analyze the effectiveness and influence of keyword-based learning skills of writing poetry with the mediation of students’ learning motivation and the moderation of teachers' teaching skills. The experimental design used was the posttest only design control group. The sample of this research is 75 students from 4 elementary schools in Mejobo Kudus district. Data collection techniques used performance tests writing poetry and questionnaires. Data analysis technique is classical assumption test include normality test and heteroscedasticity test and hypothesis test include average difference test, path analysis and moderating variable test. The results of the study showed that (1) effective keyword-based learning improves poetry writing skills, (2) keyword-based learning has a positive effect on poetry writing skill through student learning motivation and moderated teacher's teaching skill with skill findings of variation as the most optimal skill. The conclusion of the research are the effectiveness of keyword-based learning in improving students’ writing poetry skills and positive effect of the learning strategy in directly or indirectly mode on poetry writing skill with the mediation of student's learning motivation and teacher's teaching moderation.